Corporate governance practices promoting the sustainability of small, medium and microenterprises in South Africa - Medicine Magocha; Martha Matashu (AVARSITY Books, 2024)
Corporate governance practices promoting the sustainability of small, medium and microenterprises in South Africa critically examines the intersection of corporate governance and the sustainability of small enterprises. Addressing a significant gap in the literature, this scholarly work explores whether and how corporate governance frameworks enhance the long-term viability of small, medium, and microenterprises (SMMEs). Through rigorous analysis, each chapter contributes unique insights to the ongoing discourse, offering scholars a comprehensive understanding of governance mechanisms that foster resilience and growth in the SMME sector.
Keywords: 330; corporate governance; development; entrepreneurship; economic growth; small and medium enterprises (SMEs); small; medium and microenterprises (SMMEs); South Africa; sustainable development